The effect of the Covid-19 pandemic stressor on the state-trait anxiety level - Unalan, Demet; Candan, Zaliha Akkadin; Baynal Dogan, Tugba Gul; Dogan, Sermed; Baydur, Hakan (Journal of the Pakistan Medical Association, 2022)
Objectives: To evaluate the effect that the coronavirus diseases-2019 pandemic will likely have on public and its impact on the state-trait anxiety level of the masses. Methods: The cross-sectional study was conducted from May 28 to June 5, 2020, in Turkey, with Kayseri province being the first ring of the chain, and comprised adult citizens of either gender living in Turkey during the pandemic period who could use online technologies. The Impact of Event Scale-Revised was used to determine the effects of the pandemic on the public, and the State Anxiety Inventory and the Trait Anxiety Inventory were used to determine the anxiety level of the public. Data was analysed using SPSS 25 and Stata 14. Results: Of the 1507 subjects, 862(57.2%) were females and 645(42.8%) were males. The largest age group was 18-29 years with 573(38%) sucjects, while the smallest group was aged >60 years with 53(3.5%) subjects. The mean score of State Anxiety Inventory was 39.3±11.3 and mean Trait Anxiety Inventory score was 42.8±8.7, while the Impact of Event Scale-Revised mean score was 27.4±14.5. Each one unit increase in the Impact of Event Scale-Revised total score increased state anxiety score 1.10 times and trait anxiety score 1.07 times. Conclusions: Increasing age had a protective effect on state-trait anxiety. Consequently, an increase in Impact of Event Scale-Revised score led to an increase in the anxiety level. Key Words: COVID-19, Anxiety level, Impact of event. Continue....